2012
DOI: 10.1093/arclin/acr094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Exercise on Executive Function in Children with Attention Deficit Hyperactivity Disorder

Abstract: This study was conducted to determine the effect of acute aerobic exercise on executive function in children with attention deficit hyperactivity disorder (ADHD). Forty children with ADHD were randomly assigned into exercise or control groups. Participants in the exercise group performed a moderate intensity aerobic exercise for 30 min, whereas the control group watched a running/exercise-related video. Neuropsychological tasks, the Stroop Test and the Wisconsin Card Sorting Test (WCST), were assessed before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
237
1
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(274 citation statements)
references
References 62 publications
13
237
1
23
Order By: Relevance
“…Within the pediatric literature, the Stroop Test has been used to assess executive dysfunctions in several children illness groups, including Traumatic Brain Injury (Max et al, 2013), benign focal childhood epilepsy (Kernan et al, 2012), leukemia (Kim et al, 2015), Attention Deficit Hyperactivity Disorder (Assef, Capovilla, & Capovilla, 2007;Chang, Liu, Yu, & Lee, 2012), autism (Lai et al, 2016), learning disabilities (Westendorp, Hartman, Houwen, Smith, & Visscher, 2014), as well as prenatal exposure to alcohol, cocaine and tobacco (Gautam, Warner, Kan, & Sowell, 2015;Lebel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within the pediatric literature, the Stroop Test has been used to assess executive dysfunctions in several children illness groups, including Traumatic Brain Injury (Max et al, 2013), benign focal childhood epilepsy (Kernan et al, 2012), leukemia (Kim et al, 2015), Attention Deficit Hyperactivity Disorder (Assef, Capovilla, & Capovilla, 2007;Chang, Liu, Yu, & Lee, 2012), autism (Lai et al, 2016), learning disabilities (Westendorp, Hartman, Houwen, Smith, & Visscher, 2014), as well as prenatal exposure to alcohol, cocaine and tobacco (Gautam, Warner, Kan, & Sowell, 2015;Lebel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tantillo et al (2002) reported that motor impersistence score improved following a graded exercise to maximum in boys, but not girls with ADHD or in a control group. Studies by Chang et al (2012), Medina et al (2010), and Pontifex et al (2013) also reported acute exercise improved behavior-based assessments in children with ADHD. The study by Medina et al is particularly interesting because they employed an exercise bout nearly identical to the exercise bout used in the present study and showed improved performance on 6 of 13 measurements from the CCPT II in comparison to a control (stretching exercise) condition.…”
Section: Discussionmentioning
confidence: 93%
“…However, this outcome is in accordance with results reported by Craft (1983) who found that exercise durations of 1-, 5-and 10-mnutes at a heart rate of ~170 bpm had no effect on cognitive performance on the WISC-R (Digit Span and Coding B) and the Illinois Test of Psycholinguistic Abilities in hyperactive boys compared to a no exercise trial. In contrast, there are a number of studies reporting positive effects of a single bout of exercise on neurocognitive function in children with ADHD (Chang, et al, 2012;Medina, et al, 2010;Pontifex, et al, 2013;Tantillo, et al, 2002). For example, Tantillo et al (2002) reported that motor impersistence score improved following a graded exercise to maximum in boys, but not girls with ADHD or in a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por un lado, Chang et al (2012), observaron que tras 30min de AF a intensidad moderada-vigorosa en tapiz rodante ____intensidad 50-70% FCM____, 20 jóvenes diagnosticados TDAH, con edades de entre de 8-15 años mejoraron las funciones ejecutivas y procesamiento de planificación en jóvenes frente a los 20 jóvenes que formaron el grupo control. Por otro lado, Liu & Hamilton (2013) obtuvieron mejoras en la cognición y comportamientos estereotipados y repetitivos son en una muestra de 23 jóvenes diagnosticados TEA, de entre 5-13 años de edad, tras la práctica de 15min de AF a intensidad moderada-vigorosa.…”
Section: Discusión/conclusionesunclassified